Parents who supply sips of alcohol in early adolescence: A prospective study of risk factors - Wadolowski, M.; Hutchinson, D.; Bruno, R.; Aiken, A.; Najman, J.; Kypri, K.; Slade, T.; McBride, Nyanda; Mattick, R. (American Academy of Pediatrics, 2016)
Copyright © 2016 by the American Academy of Pediatrics. BACKGROUND: Parents are a major supplier of alcohol to adolescents, often initiating use with sips. Despite harms of adolescent alcohol use, research has not addressed the antecedents of such parental supply. This study investigated the prospective associations between familial, parental, peer, and adolescent characteristics on parental supply of sips. METHODS: Participants were 1729 parent-child dyads recruited from Grade 7 classes, as part of the Australian Parental Supply of Alcohol Longitudinal Study. Data are from baseline surveys (Time 1) and 1-year follow-up (Time 2). Unadjusted and adjusted logistic regressions tested prospective associations between Time 1 familial, parental, peer, and adolescent characteristics and Time 2 parental supply. RESULTS: In the fully adjusted model, parental supply was associated with increased parentreport of peer substance use (odds ratio [OR] = 1.20, 95% confidence ratio [CI], 1.08-1.34), increased home alcohol access (OR = 1.07, 95% CI, 1.03-1.11), and lenient alcohol-specific rules (OR=0.88, 95% CI, 0.78-0.99). CONCLUSIONS: Parents who perceived that their child engaged with substance-using peers were more likely to subsequently supply sips of alcohol. Parents may believe supply of a small quantity of alcohol will protect their child from unsupervised alcohol use with peers. It is also possible that parental perception of peer substance use may result in parents believing that this is a normative behavior for their child's age group, and in turn that supply is also normative. Further research is required to understand the impacts of such supply, even in small quantities, on adolescent alcohol use trajectories.